2020
DOI: 10.1080/02770903.2020.1728767
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns among non-active users of maintenance asthma medication in the United Kingdom: a retrospective cohort study in the Clinical Practice Research Datalink

Abstract: Objective: To describe patient characteristics, treatment patterns and healthcare utilization (HCU) of non-active users of maintenance asthma medications in the United Kingdom. Methods: Retrospective, cohort analysis of patients with asthma, aged ! 6 years who were non-active users of maintenance therapy (no prescription for inhaled corticosteroids (ICS), combined ICS/long-acting beta agonists (ICS/LABA) or 'other' bronchodilatory therapies in last 12 months) were identified in the Clinical Practice Research D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
2
17
4
Order By: Relevance
“…Our investigation highlights the risks of under-treatment with ICS, which can occur with ICS/formoterol as-needed regimens in mild persistent asthma, as recommended by GINA [ 1 ]. As asthma is a chronic inflammatory disease, periods with sub-optimal bronchoprotection may lead to increased inflammation, risk of exacerbation, and in the long term a greater risk of declining lung function and airway remodelling [ 31 , 33 36 , 50 ]. Indeed, our findings are relevant to the current GINA treatment recommendations in mild asthma [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation highlights the risks of under-treatment with ICS, which can occur with ICS/formoterol as-needed regimens in mild persistent asthma, as recommended by GINA [ 1 ]. As asthma is a chronic inflammatory disease, periods with sub-optimal bronchoprotection may lead to increased inflammation, risk of exacerbation, and in the long term a greater risk of declining lung function and airway remodelling [ 31 , 33 36 , 50 ]. Indeed, our findings are relevant to the current GINA treatment recommendations in mild asthma [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMP PC 20 \80 mg/mL using a wide range of dilutions (0.04, 0.08, 0.16, 0.32, 0.63, 1.25, 2.5, 5.0, 10.0, 20.0, 40.0, 80.0, 160.0 and 320.0 mg/mL) and had a mean baseline value AMP PC 20 of 15.15 mg/mL (SD 16.3 mg/mL). Each study period comprised five dose escalations (lg/day) of 7 days duration: FF (25,100,200,400,800), FP (50,200,500,1000,2000), BUD (100, 400, 800, 1600, 3200) or placebo, with a 25-to 42-day washout period between exposures. At the end of each escalation, 12 h post-dose, the AMP PC 20 was assessed.…”
Section: Clinical Datamentioning
confidence: 99%
“…In a recent survey of physicians in Asia, in addition to treatment guidelines and physician's personal experience, patient affordability of treatment was identified as an important factor influencing the choice of treatment by physicians for patients with asthma and co-existent rhinitis (45). Although hospitalizations due to asthma pose a significant cost, medications are the major contributor to overall costs of maintenance-treatment asthma management (1,46), since there are many patients with asthma but only a relative minority experience hospital admission (4,46). The data from our analysis showed that costs of medication was the most important driver of direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of a patient's asthma is based on the level of treatment required to control symptoms and to minimize the risk of exacerbations and, in this context, moderate asthma is defined as asthma that is well controlled with low dose daily inhaled corticosteroid (ICS) and long-acting beta-2-agonist (LABA) combinations comprising either regular maintenance therapy with ICS/LABA plus as-needed short-acting beta-2-agonist (SABA) as reliever therapy or ICS-formoterol combinations used as both maintenance and reliever therapy (MART) (1). Approximately 10-30% of patients with asthma are reported to experience exacerbations (2)(3)(4). Although poor asthma control and risk of exacerbation are related, they are not exactly concordant (5) and it is therefore important to assess both separately when considering treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, primary care is the first place of contact [28,29]. Primary care physicians (PCPs) deal with many other asthma challenges, including access to asthma medicines, spacer device availability, patient adherence to treatment regimens, implementation of a written asthma action plan, difficult access to care in rural areas and the demand of patients' everyday work and life [29][30][31][32]. Many asthmarelated deaths can be prevented by better education, use of asthma action plans, more accurate and timely diagnosis, rapid referral to a respiratory specialist when needed, better follow-up, and encouragement to continue taking regular preventative medicines [33,34].…”
Section: Introductionmentioning
confidence: 99%